2015
DOI: 10.1080/15384101.2015.1078034
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA Linc00152 is involved in cell cycle arrest, apoptosis, epithelial to mesenchymal transition, cell migration and invasion in gastric cancer

Abstract: Gastric cancer remains a serious threat to public health with high incidence and mortality worldwide. Accumulating evidence demonstrates that long non-coding RNAs (lncRNAs) play important roles in regulating gene expression and are involved in various pathological processes, including gastric cancer. To investigate the possible role of dysregulated lncRNAs in gastric cancer development, we performed lncRNA microarray and identified 3141 significantly differentially expressed lncRNAs in gastric cancer tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
200
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(218 citation statements)
references
References 39 publications
15
200
2
1
Order By: Relevance
“…As a novel LncRNA, Linc00152 is increased in several cancers and exerts multiple functions to influence the tumor progression. [26][27][28] In this study, we report for the first time that Linc00152 promotes L-OHP resistance in colon cancer cells in vitro and in vivo. Mechanistically, Linc00152 confers resistance to L-OHP by competitively binding miR-193a-3p, upregulating ERBB4, and then inducing the activation of AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 68%
“…As a novel LncRNA, Linc00152 is increased in several cancers and exerts multiple functions to influence the tumor progression. [26][27][28] In this study, we report for the first time that Linc00152 promotes L-OHP resistance in colon cancer cells in vitro and in vivo. Mechanistically, Linc00152 confers resistance to L-OHP by competitively binding miR-193a-3p, upregulating ERBB4, and then inducing the activation of AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 68%
“…LncRNAs have been shown to influence a number of cellular functions, such as cell proliferation, migration, invasion, and apoptosis, by modulating gene expression at transcriptional and posttranscriptional levels [4-7]. Recently, Zhao et al have performed a lncRNA microarray analysis of gastric tumors and found 3141 lncRNAs which were significantly differentially expressed in tumor tissue compared to the paired normal gastric tissue [8]. It has been reported that H19, a 2.3-kb lncRNA which is transcribed from H19/Igf2 gene cluster located on human chromosome 11p15.5, is among the strongly upregulated lncRNAs [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in lung cancer cells, upregulation of the lncRNA HOX transcript antisense RNA (HOTAIR) enhances cell proliferation, migration and invasion (8). In gastric cancer, the lncRNA Linc00152 is involved in cell cycle arrest, migration, invasion, apoptosis and the epithelial to mesenchymal (ETM) transition of cancer cells (9). Similarly, the lncRNA Linc00617 has been found to have oncogenic activity in breast cancer (10).…”
Section: Introductionmentioning
confidence: 99%